Pengaruh Pemberian Ekstrak Etanol Daun Patikan Kebo (Euphorbia Hirta L.) Terhadap Kadar Ldl Pada Mencit Putih Jantan - Surya Dharma; Hendri Fatriona; Elisma Elisma (STIFARM Padang, 2013)
Study about the influence of Euphorbia hirta L. leaves’s aethanolic extract on the levels of blood LDL in white male mice has been done. The aethanolic extract of Euphorbia hirta L. was given orally once a day for 7 th, 14 th and 21 th days.The doses used were 2, 6, 18 mg/ 20g body weight respectively. Control group was given standard food. Parameter was measured level of blood LDL. The result show that the aethanolic extract of Euphorbia hirta L. does not influence to the levels of LDL, while the time factor for 7 th, 14 th and 21 th days showed a significant effect (p <0.05).